(untitled) (Práxis Educativa, 2022)
This essay is more than anything an invitation, a message that comes from our grounds of belonging, from our experiences in the search to learn to read the world beyond what the paper skins (books) tell us. Forging other ways of learning / teaching, of building an Afro-referenced education mediated by African philosophies that are woven by traditions, values ​​and cultures preserved and transmitted by ancestral memories embroidered on our bodies, in daily practices of solidarity, care, respect for nature, our sensibilities, to ancestry. It is an invitation to sensitive listening, to learn by listening to elderly people who present us with other tools for building an education for harmonic, plural and integrative ethnic racial relations. Keywords: Seniority. Afro-referenced methodologies. Education for Ethnic-Racial Relations (ERER).